Area Of A Triangle!

Geometry Level 3

In the diagram above A B = 2 B C AB = 2BC , A B D D B C = 6 0 \angle{ABD} \cong \angle{DBC} = 60^{\circ} and B D = a BD = a . Find the value of a a for which the area of A B C \triangle ABC is 11250 3 11250\sqrt{3} .

Note: B D BD is not an altitude of A B C \triangle{ABC} .


The answer is 100.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Jan 19, 2020

Let B C = x BC = x ; then A B = 2 x AB = 2x . Let B A C = θ \angle BAC = \theta . By sine rule ,

{ A B B D = sin A D B sin B A D 2 x a = sin ( 12 0 θ ) sin θ . . . ( 1 ) B C B D = sin B D C sin B C D x a = sin ( 6 0 + θ ) sin ( 6 0 θ ) . . . ( 2 ) \begin{cases} \dfrac {AB}{BD} = \dfrac {\sin \angle ADB}{\sin \angle BAD} & \implies \dfrac {2x}a = \dfrac {\sin (120^\circ - \theta)}{\sin \theta} & ...(1) \\ \dfrac {BC}{BD} = \dfrac {\sin \angle BDC}{\sin \angle BCD} & \implies \dfrac xa = \dfrac {\sin (60^\circ + \theta)}{\sin (60^\circ -\theta)} & ...(2) \end{cases}

( 1 ) ( 2 ) : 2 = sin ( 12 0 θ ) sin θ × sin ( 6 0 θ ) sin ( 6 0 + θ ) Note that sin ( 18 0 ϕ ) = sin ϕ = sin ( 6 0 + θ ) sin θ × sin ( 6 0 θ ) sin ( 6 0 + θ ) = sin ( 6 0 θ ) sin θ = 3 2 cot θ 1 2 \begin{aligned} \frac {(1)}{(2)}: \quad 2 & = \frac {\blue{\sin(120^\circ - \theta)}}{\sin \theta} \times \frac {\sin(60^\circ - \theta)}{\sin (60^\circ+\theta)} & \small \blue{\text{Note that }\sin (180^\circ - \phi) = \sin \phi} \\ & = \frac {\blue{\sin(60^\circ + \theta)}}{\sin \theta} \times \frac {\sin(60^\circ - \theta)}{\sin (60^\circ+\theta)} \\ & = \frac {\sin(60^\circ - \theta)}{\sin \theta} \\ & = \frac {\sqrt 3}2 \cot \theta - \frac 12 \end{aligned}

tan θ = 3 5 sin θ = 21 14 , cos θ = 5 7 14 \implies \tan \theta = \dfrac {\sqrt 3}5 \implies \sin \theta = \dfrac {\sqrt{21}}{14}, \cos \theta = \dfrac {5\sqrt 7}{14} and from ( 1 ) (1) :

2 x a = sin ( 6 0 + θ ) sin θ = 3 2 × 5 7 14 + 1 2 × 21 14 21 14 = 3 x = 3 2 a A A B C = 1 2 A B × B D sin 6 0 + 1 2 B C × B D sin 6 0 = 1 2 ( 2 x + x ) a ( 3 2 ) = 9 3 8 a 2 = 11250 3 a = 8 × 11250 9 = 100 \begin{aligned} \frac {2x}a & = \frac {\sin (60^\circ + \theta)}{\sin \theta} = \frac {\frac {\sqrt 3}2 \times \frac {5\sqrt 7}{14} + \frac 12 \times \frac {\sqrt{21}}{14}}{\frac {\sqrt {21}}{14}} = 3 \\ \implies x & = \frac 32 a \\ A_{\triangle ABC} & = \frac 12 AB \times BD \sin 60^\circ + \frac 12 BC \times BD \sin 60^\circ \\ & = \frac 12 (2x+x) a \left(\frac {\sqrt 3}2\right) \\ & = \frac {9\sqrt 3}8 a^2 = 11250 \sqrt 3 \\ \implies a & = \sqrt{\frac {8 \times 11250}9} = \boxed{100} \end{aligned}

Rocco Dalto
Jan 18, 2020

Using the Law of sines for A B D \triangle{ABD} we have:

2 3 A D = 2 y sin ( 18 0 m ) = 2 y sin ( m ) \dfrac{2}{\sqrt{3}}AD = \dfrac{2y}{\sin(180^{\circ} - m)} = \dfrac{2y}{\sin(m)} \implies A D = 3 y sin ( m ) AD = \dfrac{\sqrt{3}y}{\sin(m)}

and using the Law of sines for D B C \triangle{DBC} we have:

2 3 D C = y sin ( m ) D C = 3 y 2 sin ( m ) \dfrac{2}{\sqrt{3}}DC = \dfrac{y}{\sin(m)} \implies DC = \dfrac{\sqrt{3}y}{2\sin(m)}

A D D C = 2 \implies \dfrac{AD}{DC} = 2 .

Let D C = x A D = 2 x DC = x \implies AD = 2x .

Using the Law of cosines for A B D \triangle{ABD} we have:

4 x 2 = 4 y 2 + a 2 4 a y cos ( 6 0 ) = 4 y 2 2 a y + a 2 4x^2 = 4y^2 + a^2 - 4ay\cos(60^{\circ}) = 4y^2 - 2ay + a^2

and using the Law of cosines for D B C \triangle{DBC} we have:

x 2 = y 2 + a 2 2 a y cos ( 6 0 ) = y 2 a y + a 2 x^2 = y^2 + a^2 - 2ay\cos(60^{\circ}) = y^2 - ay + a^2

Solving the two equations:

4 x 2 = 4 y 2 2 a y + a 2 4x^2 = 4y^2 - 2ay + a^2

4 ( x 2 = y 2 a y + a 2 ) -4 (x^2 = y^2 - ay + a^2)

2 a y 3 a 2 = 0 a ( 2 y 3 a ) = 0 \implies 2ay - 3a^2 = 0 \implies a(2y - 3a) = 0 and a 0 y = 3 a 2 a \neq 0 \implies y = \dfrac{3a}{2}

x 2 = 9 4 a 2 3 2 a 2 + a 2 = 7 4 a 2 x = 7 2 a \implies x^2 = \dfrac{9}{4}a^2 - \dfrac{3}{2}a^2 + a^2 = \dfrac{7}{4}a^2 \implies x = \dfrac{\sqrt{7}}{2}a

D C = 7 2 a = 3 ( 3 2 ) a 2 sin ( m ) \implies DC = \dfrac{\sqrt{7}}{2}a = \dfrac{\sqrt{3}(\dfrac{3}{2})a}{2\sin(m)} \implies sin ( m ) = 3 2 3 7 \sin(m) = \dfrac{3}{2}\sqrt{\dfrac{3}{7}} and B D = a BD = a \implies

the height h h of A B C \triangle{ABC} is h = 3 2 3 7 a h = \dfrac{3}{2}\sqrt{\dfrac{3}{7}}a

and A C = a A A B C = 1 2 ( 3 7 2 ) ( 3 2 ) 3 7 a 2 = 9 8 3 a 2 = 11250 3 = AC = a \implies A_{\triangle{ABC}} = \dfrac{1}{2}(\dfrac{3\sqrt{7}}{2})(\dfrac{3}{2})\sqrt{\dfrac{3}{7}} a^2 = \dfrac{9}{8}\sqrt{3} a^2 = 11250\sqrt{3} =

2 2 5 2 3 2 3 a 2 = 2 4 ( 25 ) 2 a = 100 2 * 25^2 * 3^2\sqrt{3} \implies a^2 = 2^4 * (25)^2 \implies a = \boxed{100} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...